TMOD-08. GROWTH IMPAIRMENT UNDER CONDITIONS FAVORING MITOCHONDRIAL OXIDATIVE METABOLISM IN A YEAST MODEL OF CANCER-ASSOCIATED ISOCITRATE DEHYDROGENASE MUTATION. (5th November 2018) - Fiola, Sophie; Ganni, Elie; Lo, Rita; Kuzmin, Elena; Diaz, Roberto
Abstract: The use of the budding yeast Saccharomyces cerevisiae as a model system to study cancer allows for faster, more efficient elucidation of various molecular mechanisms, including mutation rate by fluctuation analysis, cell cycle analysis by flow cytometry, metabolism via growth rate analysis, and functional genomics via genomic array screening. The vast majority of low grade gliomas (LGGs) carry somatic mutations in isocitrate dehydrogenase 1 (IDH1 ) and 2 ( IDH2 ) genes. IDH1 and IDH2 catalyze the oxidative decarboxylation of isocitrate to a-ketoglutarate (a-KG) in an NADP + dependent manner. A point mutation (R132H in IDH1 and R172H in IDH2) confers the neomorphic ability for the enzyme reduce a-KG to D-2-hydroxyglutarate (D2-HG). In S. cerevisae, the NADP + dependent isocitrate dehydrogenases are encoded by three different genes, IDP1, IDP2 and IDP3 . We have successfully generated a yeast model that carries the analogous mutation in the yeast IDP1 gene (IDP1 R148H ). The allele was inserted at the HO locus, which does not alter the endogenous IDP1 gene. In this way, the resulting strain carries both a wild-type and mutant allele of IDP, more closely mimicking the metabolic state of glioma cells. We have validated this insertion by PCR, sequencing, and tetrad analysis. The production of the mutant IDP1 R148H protein was detected by Western blot. The IDP1 R148H strain shows normal growth on glucose and galactose-containing solid media, but reduced growth on glycerol-containing solid media compared to parental or IDP1 WT strains. Impaired growth of yeast when glycerol is the sole carbon source suggests a defect in mitochondrial oxidative metabolism. This observation is consistent with a previous yeast IDP1 R148H model which showed extensive mitochondrial DNA loss and respiration defects. Taken together, we have developed a model of IDH-mutant LGGs in S. cerevisiae that can be further utilized to study molecular mechanisms underlying tumorigenesis of LGGs.